Old Nick Crossed the Mississippi: The Figure of the Devil in Late Cold War Era Novels of the American West - Michael Walonen (European Journal of American Studies)
The figure of the devil – employed time and again by Americans as a means of culturally construing the perceived enemy Other, as W. Scott Poole illustrates in his study Satan in America – appears with great frequency within the corpus of the literature of the American West. This essay focuses on Western regional novels of the late Cold War period (1968-1991), analyzing their manner of using the devil figure to variously challenge and/or reinforce mainstream conceptions of evil and come to terms with the meaning and direction of America at a time of crossroads and vast social transfiguration. It argues that Stephen King’s The Stand (1978) employs the satanic Randall Flagg to interrogate what is taken as an intrinsic strain of evil running through America’s history and emerging in especially pointed form in the social unrest and malaise of the late 1960s and 1970s. Cormac McCarthy’s Blood Meridian (1985), on the other hand, attributes Mephistophelean attributes (among others) to its antagonist Judge Holden as a means of dramatizing how barbarity, destruction, and expenditure are inexorably intertwined with the values and goals of civilization, while Ishmael Reed’s Yellow Back Radio Broke-Down (1969) reconfigures and repurposes the devil figure, drawing on the cultural valences of pagan male fertility figures and the Africana traditions he elsewhere conceptualizes as “neo-hoodoo” to wage a counter-cultural attack upon the pillars of American and Western Christian society.